The role of the elderly in the preservation and dissemination of terena ethnoknowledge in indigenous school in Mato Grosso do Sul state - Vilarim, Paulo Roberto (2022)
In this article, the authors analyze the elders’ role in the preservation and dissemination of Terena ethnoknowledge in the context of formal school, a public institution as a mediator between scientific knowledge constituted in the West and traditional knowledge built throughout the history of an original people. The main objective of the work is to analyze how teachers, from public schools existing in Terena villages, located in Mato Grosso do Sul state, Brazil, use traditional knowledge of diverse knowledge to indigenous students’ transmission. Terena teachers tend to point out the relevant role of the wise elders as transmitters of traditional knowledge and highlight their importance for the education of students, it being up to the teachers to understand this knowledge and apply it in their pedagogical practices.